The Association between Grandmaternal Investment and Early Years Overweight in the UK - Antti O. Tanskanen (Evolutionary Psychology, 2013)
Previous studies show that in many pre-modern and traditional populations the presence of a grandmother correlates with increased child survival rates, maybe as a result of improved child nutrition. Grandmaternal investment aimed at improving grandchildren's nutritional status in subsistence societies may have different outcomes in contemporary affluent societies. Using the British Millennium Cohort Study I investigate the association between maternal and paternal grandmothers' childcare and early years overweight in the UK. Results show that children who were cared for mainly by their grandmothers between the ages of 9 months and 3 years were more likely overweight at age 3 than children who were cared for by their parents. My results are in line with Pearce, Abbas, Ferguson, Graham, and Law (2010) , although they did not distinguish grandmothers by lineage. Grandmothers may influence children's nutritional status in contemporary societies, but as with many evolved behavioral strategies the outcome may be no longer beneficial.